MANIFESTASI KLINIS DAN TATALAKSANA UVEITIS TUBERKULOSIS : CLINICAL MANIFESTATIONS AND MANAGEMENT OF TUBERCULOSIS UVEITIS - Kenya Brilliantyas; Raja Merlinda Veronica (Jurnal Kedokteran STM (Sains dan Teknologi Medik), 2026)
Tuberculous uveitis is a form of extrapulmonary tuberculosis characterized by a broad spectrum of clinical manifestations and significant diagnostic challenges. The condition may result from direct invasion of Mycobacterium tuberculosis into ocular tissues or from an immune-mediated response to mycobacterial antigens. Clinical presentations vary widely, including anterior, intermediate, posterior, and panuveitis, with posterior uveitis being the most commonly observed form. Diagnosis is largely presumptive, based on a combination of clinical findings, immunological tests such as interferon-gamma release assays or tuberculin skin tests, chest imaging, and response to anti-tuberculosis therapy. The mainstay of treatment involves anti-tuberculosis therapy combined with corticosteroids to control intraocular inflammation. This combined approach has been shown to improve visual outcomes and reduce inflammatory activity more effectively than monotherapy. Prognosis depends on early diagnosis and timely treatment, with better outcomes achieved when managed promptly. However, complications such as cataract, glaucoma, and macular edema remain significant concerns, highlighting the importance of a multidisciplinary approach in clinical managementMorbi a commodo erat. Aenean tincidunt dapibus quam, sit amet vulputate ligula. Maecenas a suscipit velit. AbstrakUveitis tuberkulosis merupakan salah satu manifestasi tuberkulosis ekstraparu yang memiliki spektrum klinis luas dan sering menimbulkan tantangan dalam penegakan diagnosis. Penyakit ini dapat terjadi akibat invasi langsung Mycobacterium tuberculosis ke jaringan okular maupun sebagai respons imun terhadap antigen bakteri. Manifestasi klinisnya bervariasi, meliputi uveitis anterior, intermediat, posterior, hingga panuveitis, dengan posterior uveitis sebagai bentuk yang paling sering ditemukan. Diagnosis umumnya bersifat presumtif dengan menggabungkan temuan klinis, pemeriksaan imunologis seperti IGRA atau uji tuberkulin, pencitraan toraks, serta respons terhadap terapi. Penatalaksanaan utama adalah pemberian terapi anti-tuberkulosis yang dikombinasikan dengan kortikosteroid untuk mengendalikan inflamasi intraokular. Kombinasi terapi ini terbukti memberikan perbaikan tajam penglihatan dan resolusi inflamasi yang lebih baik dibandingkan terapi tunggal. Prognosis bergantung pada kecepatan diagnosis dan inisiasi terapi, dengan luaran yang lebih baik pada penanganan dini. Namun, risiko komplikasi seperti katarak, glaukoma, dan edema makula tetap menjadi perhatian. Oleh karena itu, pendekatan multidisiplin dan kewaspadaan klinis yang tinggi sangat diperlukan untuk meningkatkan hasil terapi.